Implementation of Human Resource Management at MAN 1 Cilacap - Ulil Albab; Dian Permana; Misbahus Surur; Ahmad Zulfi Fahmi (Trescode Green Organization, 2025)
This study aims to describe the implementation of human resource management in the context of educational institutions in schools. This type of research is descriptive qualitative, which is research conducted in actual conditions. The research subject is the vice principal of the curriculum. Data collection was done by observation, interview, and documentation. Data analysis used the Miles and Hubberman interactive analysis model, namely data collection, data reduction, data presentation and conclusion drawing. Meanwhile, data validity was tested by triangulating data techniques and sources. The results showed that the implementation of human resource management at MAN 1 Cilacap has been well implemented, characterised by the existence of human resource planning, recruitment and selection of professional and transparent human resources, training and development, performance management.